2002
DOI: 10.1257/000282802762024746
|View full text |Cite
|
Sign up to set email alerts
|

Protection for Sale: An Empirical Investigation: Comment

Abstract: Do contributions levels matter for endogenous protection or is the existence of a lobby sufficient? Are lobbies' net benefits from protection identical to their contribution levels, or does the level of protection simply reflect contribution levels of supporters and opponents? We estimate the Influence Driven (Grossman and Helpman, 1994) and the Tariff Function (Findlay and Wellisz, 1982) models within a unified theoretical framework to examine the contrasting implications derived from these two prominent tari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 16 publications
5
65
2
Order By: Relevance
“…Comparing the "Heterogeneity" model and the "Protection for sale" model It is difficult to draw any sharp conclusions from comparing results from specifications (14) and (17) because the two models are such that model (17) is not nested into model (14). I adopt a methodology introduced by Davidson and MacKinnon (1981) and employed by Eicher and Osang (2002) to compare the two models' power in explaining the pattern of protection across sectors. The 46 The average coverage ratio is 0:1 with a standard deviation of 0.2.…”
Section: The Heterogeneity Specification With Constructed Participatimentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the "Heterogeneity" model and the "Protection for sale" model It is difficult to draw any sharp conclusions from comparing results from specifications (14) and (17) because the two models are such that model (17) is not nested into model (14). I adopt a methodology introduced by Davidson and MacKinnon (1981) and employed by Eicher and Osang (2002) to compare the two models' power in explaining the pattern of protection across sectors. The 46 The average coverage ratio is 0:1 with a standard deviation of 0.2.…”
Section: The Heterogeneity Specification With Constructed Participatimentioning
confidence: 99%
“…Both test I and II support the Heterogeneity model. Also see Eicher and Osang (2002). 55 These results are particularly relevant if one believes that the True Participation Shares might be measured with error and the Constructed Participation Shares can be considered a theoretically justified instrument.…”
mentioning
confidence: 94%
“…Most of the empirical literature has focused on the United States (US) and found that domestic lobbying is a significant determinant of US trade policy (see Gawande, 1997;Goldberg and Maggi, 1999;Gawande and Bandhopadhyay, 2000;Eicher and Osang, 2002;Matschke and Sherlund, in press). 3 More recently, Gawande, Krishna, and Robbins (2004) introduced foreign lobbying into the Grossman and Helpman (1994) model.…”
Section: Introductionmentioning
confidence: 99%
“…The lobby groups choose these schedules simultaneously and non-cooperatively with the anticipation of government's movement in the second stage. Some of the empirical studies in this area are: Goldberg and Maggi (1999), Gawande and Bandyopadhyay (2000), Eicher and Osang (2002), Mitra, Thomakos, and Ulubasoglu (2002) Gawande, Krishna, and Robbins (2006), and Matschke (2008). in the third stage, the production and consumption decisions are made. Then subsequently, 1 Grossman and Helpman's paper has been the most influential one in terms of both theory and empirical estimation of endogenous trade policy.…”
Section: Introductionmentioning
confidence: 99%